Numerical Flow Modeling of Artificial Ocean Upwelling - Kemper, Jost; Riebesell, Ulf; Graf, Kai (Frontiers in Marine Science, 2022)
Artificial Upwelling (AU) of nutrient-rich Deep Ocean Water (DOW) to the ocean’s sunlit surface layer has recently been put forward as a means of increasing marine CO2 sequestration and fish production. AU and its possible benefits have been studied in the context of climate change mitigation as well as food security for a growing human population. However, extensive research still needs to be done into the feasibility, effectiveness and potential risks, and side effects associated with AU to be able to better predict its potential. Fluid dynamic modeling of the AU process and the corresponding inorganic nutrient transport can provide necessary information for a better quantification of the environmental impacts of specific AU devices and represents a valuable tool for their optimization. Yet, appropriate capture of all flow phenomena relevant to the AU process remains a challenging task that only few models are able to accomplish. In this paper, simulation results obtained with a newly developed numerical solution method are presented. The method is based on the open-source modeling environment OpenFOAM. It solves the unsteady Reynolds-Averaged Navier-Stokes (RANS) equations with additional transport equations for energy, salinity, and inorganic nutrients. The method aims to be widely applicable to oceanic flow problems including temperature- and salinity-induced density stratification and passive scalar transport. The studies presented in this paper concentrate on the direct effects of the AU process on nutrient spread and concentration in the ocean’s mixed surface layer. Expected flow phenomena are found to be captured well by the new method. While it is a known problem that cold DOW that is upwelled to the surface tends to sink down again due to its high density, the simulations presented in this paper show that the upwelled DOW settles at the lower boundary of the oceans mixed surface layer, thus keeping a considerable portion of the upwelled nutrients available for primary production. Comparative studies of several design variants, with the aim of maximizing the amount of nutrients that is retained inside the mixed surface layer, are also presented and analyzed.